Effect of Agricultural Credit on the Growth of Agricultural Sector in Nepal - Rawat, Shankar Kumar (Journal of Emerging Management Studies, 2024)
Purpose – The research aims to examine the effect of agricultural credit on agricultural GDP growth in Nepal. Design/methodology/approach – Utilizing secondary data from the Ministry of Finance, Nepal Rastra Bank, and the Department of Hydrology and Meteorology spanning from 1990 to 2023, the research employed econometric techniques to explore the relationship. The research used unit root tests, co-integration analysis using the ARDL bounds test, and diagnostic tests to assess the validity of the model. Findings and Conclusion – The findings revealed a consistent decline in the relative contribution of agricultural GDP to the total GDP, indicative of a transition towards a more diversified economy. While agricultural GDP displayed fluctuations in growth rates, the sector exhibited a pattern of modest growth overall. Agricultural credit experienced fluctuations, with notable growth in the early 2010s, although a slight decline was observed in fiscal year 2022/23. Long-run relationships indicate significant positive impacts of cultivation area on agricultural GDP. The error correction model underscores the sector’s ability to adjust to shocks, emphasizing long-term stability. Implications – The findings of the research provide valuable insights into the dynamics of agricultural GDP, the role of agricultural credit and the factors influencing agricultural productivity and growth. These insights can inform agricultural policies and investment decisions aimed at promoting sustainable agricultural development and economic growth. Originality/value – The research is novel in its kind that it examines the agricultural credit performance on agricultural GDP growth in Nepal which is early research in the domain. Policymakers can use the research results to improve the effectiveness of agricultural credit and increase agricultural GDP in the country.